Treatment of peritoneal fibrosis: Therapeutic prospects of bioactive Agents from Astragalus membranaceus - Huang, Ying; Chu, Chenling; Mai, Yuanyuan; Zhao, Yue; Cao, Luxi; Ji, Shuiyu; Zhu, Bin; Shen, Quanquan (Frontiers in Pharmacology, 2024)
Peritoneal dialysis is one of the renal replacement treatments for patients with end-stage renal disease. Peritoneal dialysis-related peritoneal fibrosis is a pathological change in peritoneal tissue of peritoneal dialysis patients with progressive, non-suppurative inflammation accompanied by fibrous tissue hyperplasia, resulting in damage to the original structure and function, leading to peritoneal function failure. Currently, there is no specific drug in the clinic. Therefore, it is necessary to find a drug with good effects and few adverse reactions. Astragalus membranaceus (AMS) is the dried root of the Astragalus membranaceus (Fisch.) Bge. AMS and its active ingredients play a significant role in anti-inflammation, anti-fibrosis, regulation of immune function and regulation of blood pressure. Studies have shown that it can alleviate peritoneal fibrosis by reducing inflammatory response, inhibiting oxidative stress, degrading extracellular matrix deposition, regulating apoptosis, and regulating Transforming Growth Factor-β. The author summarized the relationship between AMS and its active ingredients by referring to relevant literature at home and abroad, in order to provide some theoretical basis for further clinical research.